Chemico-pharmacological evaluations of the dwarf elephant ear (Colocasia affinis Schott) plant metabolites and extracts: health benefits from vegetable source - Alam, Safaet; Richi, Fahmida Tasnim; Hasnat, Hasin; Ahmed, Firoj; Emon, Nazim Uddin; Uddin, Md. Jasim; Rana, G. M. Masud; Wang, Shuanghu; Yeasmin, Mst. Sarmina; Ahmed, Nazim Uddin; Khan, Md. Salim; Al Mamun, Abdullah (Frontiers in Pharmacology, 2024)
Colocasia affinis Schott (Family: Araceae), found in the Asian region, is a traditional root vegetable consumed by the locals and well-known as Dwarf Elephant Ear. For the pharmacological exploration of this root vegetable, four kupchan fractions (i.e., HSF, DCMSF, EASF, and AQSF) from ethanolic extract of C. affinis were employed to in vitro, i.e., cytotoxicity, and antimicrobial and in vivo, i.e., antidiarrheal and analgesic assays, followed by phytochemical analysis consisted of GC-MS, phytochemical screening and antioxidant assay. In the antioxidant assay, the AQSF showed promising potential with an IC50 value of 29.4 µg/mL. It exhibited the most significant overall phenolic content, measuring 57.23 mg GAE/gm. of extract, among other fractions. The AQSF also revealed promising cytotoxic activity in brine shrimp lethality assay with an LC50 value of 1.36 µg/mL. Both AQSF and EASF exhibited substantial antimicrobial efficacy against grampositive and gram-negative bacteria and various fungus species with a remarkable zone of inhibitions compared to standards. Whereas, during both the castor oil-induced antidiarrheal and acetic acid-induced writhing assay, the DCMSF at 400 mg/kg dose exhibited the highest 51.16% reduction of diarrhea and 52.33% reduction of writhing. The GC-MS study of different fractions of dwarf elephant ear ethanolic extract revealed forty-eight (48) different bioactive secondary metabolites in total. Besides, phytochemical screening also provides valuable insights into the comprehensive characterization of the chemical composition. Moreover, to validate the wet lab findings, in silico study considered several targets such as KAS, DHFR for anti-microbial activities, GLR, URO for antioxidant activities, EGFR, BCL-2 for cytotoxicity, KOR, DOR for antidiarrheal activities and COX-2, TNF-α for analgesic activities. Thus, computer-simulated molecular docking studies against identified metabolites and standards along with ADME/T studies provided promising insights into their safety, efficacy, and drug-likeliness profiles. To recapitulate, our study revealed that vegetables such as dwarf elephant ear can be considered as a prospective source of therapeutics and drug development besides their nutritive food values.